Single cell transcriptomics of bone marrow derived macrophages reveals Ccl5 as a biomarker of direct IFNAR-independent responses to DNA sensing - McCarty, Emily; Yu, Justin; Ninh, Van K.; Calcagno, David M.; Lee, Jodi; King, Kevin R. (Frontiers in Immunology, 2023)
The type I interferon (IFN) response is an innate immune program that mediates anti-viral, anti-cancer, auto-immune, auto-inflammatory, and sterile injury responses. Bone marrow derived macrophages (BMDMs) are commonly used to model macrophage type I IFN responses, but the use of bulk measurement techniques obscures underlying cellular heterogeneity. This is particularly important for the IFN response to immune stimulatory double-stranded DNA (dsDNA) because it elicits overlapping direct and indirect responses, the latter of which depend on type I IFN cytokines signaling via the IFN alpha receptor (IFNAR) to upregulate expression of interferon stimulated genes (ISGs). Single cell transcriptomics has emerged as a powerful tool for revealing functional variability within cell populations. Here, we use single cell RNA-Seq to examine BMDM heterogeneity at steady state and after immune-stimulatory DNA stimulation, with or without IFNAR-dependent amplification. We find that a large number of macrophages express ISGs after DNA stimulation. We also find that a subset of macrophages express ISGs even if IFNAR is inhibited, suggesting that they are direct responders. Analysis of this subset reveals Ccl5 to be an IFNAR-independent marker gene of direct DNA sensing cells. Our studies provide a method for studying direct responders to IFN-inducing stimuli and demonstrate the importance of characterizing BMDM models of innate immune responses with single cell resolution.